Building And Design Of Hydraulic Hybrid Vehicle - Mraish, Abd Almajed; Al_heimuni, Rabee' (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2010)
This project comes as a response to the modern trends In the automotive world ,and developed of hybrid technology, which could be summarized into to improving both fuel efficiency and overall operating economy of vehicles. The principle of this project is to build a hydraulic system on the rear wheels besides the vehicle original internal combustion engine for (front-wheel-drive vehicle ). The purposes of this system is to regenerative braking energy by taking the movement of the rear wheels which are connected to a hydraulic pump that compress the hydraulic fluid into a high pressure accumulator, and this energy is recovered from the accumulator to be converted into kinetic energy by the hydraulic motor to rotate the rear wheel when needed . And the other purpose of this project is that the hydraulic system can works as brake in the downgrade by operating the pump according to the wanted constant speed ,by controlling the directional control valve, this system is a flexible vehicle application and lower cost relative to any of competitive alternatives.
CD , no of page 74,24864 ,ميكانيك 10/2010 , in the store
Keywords: Hydraulic Hybrid Vehicle - Building And Design